2006
DOI: 10.1002/ardp.200600134
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of the 2,7‐Naphthyridine Alkaloids Lophocladine A and B

Abstract: The one-pot reaction of 4-benzylpyridine-3-carbonitrile with Bredereck's reagent and subsequent treatment with either glacial acetic acid and sulfuric acid or ammonium acetate provided the new bioactive naphthyridine alkaloids lophocladine A and B, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Moreover, the analyses of lophocladine B 52 effects on cellular microtubes and actin filaments in A-10 cells (used as vascular smooth muscle cells model) showed that this metabolite acts as microtubules inhibitor with no loss of actin filament [ 153 ]. In the same year Lotter et al reported that lophocladine B 52 is also able to inhibit human leukemia cells (HL-60) (IC 50 = 1 µM) [ 155 ].…”
Section: Secondary Metabolites From Seaweeds With In Vitro Cytotoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the analyses of lophocladine B 52 effects on cellular microtubes and actin filaments in A-10 cells (used as vascular smooth muscle cells model) showed that this metabolite acts as microtubules inhibitor with no loss of actin filament [ 153 ]. In the same year Lotter et al reported that lophocladine B 52 is also able to inhibit human leukemia cells (HL-60) (IC 50 = 1 µM) [ 155 ].…”
Section: Secondary Metabolites From Seaweeds With In Vitro Cytotoxmentioning
confidence: 99%
“…The well-known potential of the antitubulin compounds as effective anticancer agents, for example taxol and vincristine, spread the interest of the scientific community in the synthesis of lophocladine B 52 or derivatives, seeking new and more potent antitumor agents and/or structure activity relationship studies [ 155 , 156 , 157 , 158 ]. To date, only two of the synthesized compounds (simplified isoquinolines isoquinoline-triazole derivatives) exhibit better cytotoxicity (IC 50 = 10.14 and 12.76 µM) than lophocladine B 52 against hepatic cancer (HepG2) and cervical cancer (HeLa) cell lines (IC 50 = 89.5 and >100 µM) [ 158 ].…”
Section: Secondary Metabolites From Seaweeds With In Vitro Cytotoxmentioning
confidence: 99%
“…The annulation of the bromopyridine ring (ring E of the pyridoacridines) was accomplished in a two‐step protocol. In analogy to our total syntheses of the alkaloids perlolidine 21 and lophocladine A 29, heating of 9 with dimethylformamide diethylacetal converted the acidic methyl group at C‐4 to an enamine, which was directly cyclized to the benzo[c][2,7]naphthyridin‐4‐one 10 upon heating with conc. sulfuric acid/acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids containing the 2,7‐naphthyridine scaffold have been isolated from different kinds of living organisms. Many of these natural alkaloids show anticancer , antiviral , antifungal , and antimalarial activity. Recently, researchers have tried to obtain new 2,7‐naphthyridine derivatives, also by the synthetic route.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra were performed on a Specord M80 spectrometer (Zeiss/Analytic Jena, Germany) using KBr pellets. 1 H NMR spectra were recorded in DMSO-d6 with a Bruker Avance ARX-300 MHz spectrometer (Bruker Analytic, Karlsruhe, Germany) with tetramethylsilane as the internal standard. The new products were analyzed using a Perkin Elmer 2400 analyzer (Waltham, MA, USA).…”
mentioning
confidence: 99%